2013
DOI: 10.1002/clen.201300386
|View full text |Cite
|
Sign up to set email alerts
|

Crop Residue Ashes as Adsorbents for Basic Dye (Methylene Blue) Removal: Adsorption Kinetics and Dynamics

Abstract: In the quest for identifying low‐cost, locally available and effective adsorbents, pigeon pea (Cajanus cajan L.) residue ash (PRA) and sunflower (Helianthus annuus L.) residue ash (SRA) were evaluated as adsorbents for sequestering a basic dye, methylene blue (MB), from aqueous solution. Effects of contact time, initial solution pH and adsorbent dose on MB adsorption were investigated. MB adsorption onto PRA and SRA was dependent on initial solution pH, with adsorption being greater at higher pH. Percent MB re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The Langmuir isotherm parameters, maximum adsorption capacity ( b ) and bonding energy constant ( k ) were estimated as 169.5 mg g −1 and 0.022 L mg −1 , respectively. Further, the R L value for MB adsorption on TSB was found to be positive and less than unity (0.154), indicating favorable (0 < R L < 1) adsorption process . A comparison of adsorption capacity of different adsorbents shows that TSB for MB was found substantially superior to that of many reported low‐cost adsorbents (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Langmuir isotherm parameters, maximum adsorption capacity ( b ) and bonding energy constant ( k ) were estimated as 169.5 mg g −1 and 0.022 L mg −1 , respectively. Further, the R L value for MB adsorption on TSB was found to be positive and less than unity (0.154), indicating favorable (0 < R L < 1) adsorption process . A comparison of adsorption capacity of different adsorbents shows that TSB for MB was found substantially superior to that of many reported low‐cost adsorbents (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The ΔG value for MB adsorption onto TSB was −5.26 kJ mol −1 at room temperature (27 ± 1 ° C), indicating a spontaneous and favorable process of MB adsorption onto TSB. Further, this Δ G value is within the range (0 to −20 kJ mol −1 ) of free energy change for physi‐sorption and hence, MB adsorption onto TBS was by physi‐sorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason is that increase in dye concentration facilitates higher interaction between MB and JS. Further, higher initial dye concentration facilitates to overcome the resistance to mass transfer of MB between the adsorbent and aqueous phase [18,22,41]. The study indicated that under the studied levels of time, there was no significant difference among treatments after 60 min.…”
Section: Adsorption Of Mb Onto Jsmentioning
confidence: 90%